Mitigating off-gas emissions in the biological nitrogen removal via nitrite process treating anaerobic effluents. (15th April 2015) - Frison, Nicola; Chiumenti, Alessandro; Katsou, Evina; Malamis, Simos; Bolzonella, David; Fatone, Francesco
Abstract: A sequencing batch reactor treating the reject water produced from the dewatering of the anaerobic co-digestate of waste activated sludge and the organic fraction of municipal solid waste was monitored in order to assess the off-gas emissions that were produced. The gaseous emissions of nitrous oxide (N2 O), carbon dioxide (CO2 ), methane (CH4 ), ammonia (NH3 ) and methyl mercaptan (CH3 SH) produced during the biological nitrogen removal via nitrite route were monitored. During experimental period 1 a volumetric nitrogen loading rate (vNLR) of 1.08 kg N/m 3  d was applied, while in period 2 the vNLR was 0.81 kg N/m 3  d. Nitrous oxide emissions decreased from 1.49% of the influent nitrogen load in period 1 to 0.24% in period 2. The higher dissolved oxygen (DO) concentration and the lower accumulation of nitrite in the reactor resulted in significantly lower nitrous oxide emissions in period 2. Some methane (5.8% of influent COD load) was emitted during period 1, as the lower DO concentration created micro-anaerobic conditions within the sludge flocs. Graphical abstract: Highlights: Nitritation/denitritation of reject water can result in high off-gas emissions. N2 O emissions decreased 84% by adjusting DO, NLR and reaction sequence. Aerobic/anoxic sequence results in lower greenhouse gas peaks than the anoxic/aerobic. Low dissolved oxygen resulted in increased off-gas emissions.